Neoliberal Rationality and Neohygienist Morality. A Foucaldian Analysis of Safe and Sustainable Urban Transport Policies in France. Issue 2 (2nd April 2016) - Reigner, Hélène
Abstract: This article proposes to use Foucaldian analysis frameworks to inform us about neoliberalization, not so much from the viewpoint of political economics as in terms of the governance of individual behaviours. This theoretical ambition is based on the empirical analysis of contemporary policies in favour of safe, sustainable mobility in France. Characterized by the emphasis placed on users' individual responsibility and their capacity to adopt economically rational behaviours on the one hand and by powerful moral injunctions for them to adopt the 'right' safe, healthy, sustainable behaviours on the other, a neoliberal and neohygienist rationality feeds these public policies. Legitimated by 'noble causes' and depoliticized, these policies give a powerful organization of traffic in the city whose social challenges are evaded. The use of morality works as a powerful democratic anesthetic that dissolves any objection. An examination of Safe and Sustainable Urban Transport Policies testifies to the renewed subtle, diffuse mechanisms of domination based on free compliance and consent.